2012
DOI: 10.1016/j.cell.2012.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Exome Capture Reveals ZNF423 and CEP164 Mutations, Linking Renal Ciliopathies to DNA Damage Response Signaling

Abstract: SUMMARY Nephronophthisis-related ciliopathies (NPHP-RC) are degenerative recessive diseases that affect kidney, retina and brain. Genetic defects in NPHP gene products that localize to cilia and centrosomes defined them as ‘ciliopathies’. However, disease mechanisms remain poorly understood. Here we identify by whole exome resequencing, mutations of MRE11, ZNF423, and CEP164 as causing NPHP-RC. All three genes function within the DNA damage response (DDR) pathway, hitherto not implicated in ciliopathies. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
436
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(468 citation statements)
references
References 80 publications
18
436
1
4
Order By: Relevance
“…A number of proteins in the DNA damage response pathway, including CHK1 and ATM, appear to be enriched at centrosomes (43), and it has been suggested that mutations in specific centrosomal proteins disrupt the DNA damage response pathway (18). We did not detect any difference between E8.5 wild-type and Sas4 −/− embryos in the staining pattern of 53BP1, which marks the sites of DNA damage (Fig.…”
Section: Sas4-nullmentioning
confidence: 61%
See 1 more Smart Citation
“…A number of proteins in the DNA damage response pathway, including CHK1 and ATM, appear to be enriched at centrosomes (43), and it has been suggested that mutations in specific centrosomal proteins disrupt the DNA damage response pathway (18). We did not detect any difference between E8.5 wild-type and Sas4 −/− embryos in the staining pattern of 53BP1, which marks the sites of DNA damage (Fig.…”
Section: Sas4-nullmentioning
confidence: 61%
“…Abnormal numbers of centrioles are associated with cancer, although it is not clear whether abnormal centrosome number is a cause or an effect of tumorigenesis (1,(11)(12)(13). Studies in cultured cell lines have given conflicting results on the roles of vertebrate centrioles in mitosis, chromosome segregation, DNA damage response, and intercellular signaling (14)(15)(16)(17)(18)(19), but the precise functions of mammalian centrioles have not been defined genetically.…”
mentioning
confidence: 99%
“…Mutations in pericentrin were found to cause Seckel syndrome, a disorder characterized by reduced brain and body size, and cells from these patients showed an impairment of ATR (ATM and Rad3-related)-dependent checkpoint signalling [152]. Similarly, mutations in Cep164 were shown to cause nephronophthisis-related ciliopathies [153]. Upon DNA damage, Cep164 was reported to accumulate within nuclear foci that are implicated in the activation of ataxia telangiectasia mutated (ATM), and knockdown of Cep164 in zebrafish resulted in impaired DNA-damage response.…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…It is involved in targeting the IFT protein, IFT88, to the distal end of the centriole and possibly to the basal body [127]. Through recruitment of CEP164, a distal appendage protein mutated in cystic kidney disease, OFD1 also promotes basal body docking to the plasma membrane [114,128].…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%
“…These share many clinical features, with kidney, eye, liver and brain being the most affected organs [113]. Over the last decade, cilia have emerged as vital cellular compartments for transducing mechanical and extracellular signals, regulating organogenesis, planar polarity, proliferation, DNA damage response and autophagy [4,114,115]. Indeed, impaired signalling is considered a key underlying factor in ciliopathies.…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%